2021
DOI: 10.3390/jcm10153421
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Working Memory and Processing Speed in Patients over 70 with Bilateral Hearing Impairment Following Unilateral Cochlear Implantation

Abstract: Several studies demonstrated the association of hearing disorders with neurocognitive deficits and dementia disorders, but little is known about the effects of auditory rehabilitation on the cognitive performance of the elderly. Therefore, the research question of the present study was whether cochlear implantation, performed in 21 patients over 70 with bilateral severe hearing impairment, could influence their cognitive skills. The measuring points were before implantation and 12 months after the first cochle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 74 publications
2
17
2
1
Order By: Relevance
“…Of these, all but one demonstrated findings of subjects with dementia having increased hearing thresholds (i.e., hearing impairment) compared to controls; however, the findings of Haggstrom et al (2018) could not be used in our analysis as they reported threshold hearing loss as median-values and not mean-values. Overall, the trend of increased hearing loss in subjects with dementia compared to controls was present in both included and excluded studies, supporting both the findings of this meta-analysis and current literature (Loughrey et al, 2018;Panza et al, 2018;Ray et al, 2018;Chern and Golub, 2019;Jafari et al, 2019;Ralli et al, 2019;Mertens et al, 2020;Utoomprurkporn et al, 2020;Knopke et al, 2021). The shortcomings outlined above illustrate the importance of better characterizing peripheral hearing ability in subjects with AD compared to healthy-aging controls.…”
Section: Limitations Of the Current Studysupporting
confidence: 82%
See 3 more Smart Citations
“…Of these, all but one demonstrated findings of subjects with dementia having increased hearing thresholds (i.e., hearing impairment) compared to controls; however, the findings of Haggstrom et al (2018) could not be used in our analysis as they reported threshold hearing loss as median-values and not mean-values. Overall, the trend of increased hearing loss in subjects with dementia compared to controls was present in both included and excluded studies, supporting both the findings of this meta-analysis and current literature (Loughrey et al, 2018;Panza et al, 2018;Ray et al, 2018;Chern and Golub, 2019;Jafari et al, 2019;Ralli et al, 2019;Mertens et al, 2020;Utoomprurkporn et al, 2020;Knopke et al, 2021). The shortcomings outlined above illustrate the importance of better characterizing peripheral hearing ability in subjects with AD compared to healthy-aging controls.…”
Section: Limitations Of the Current Studysupporting
confidence: 82%
“…Due to the known positive correlation between age and hearing-loss (Loughrey et al, 2018;Panza et al, 2018;Ray et al, 2018;Chern and Golub, 2019;Jafari et al, 2019;Ralli et al, 2019;Mertens et al, 2020;Utoomprurkporn et al, 2020;Knopke et al, 2021), a pooled, standardized mean age difference was calculated. Using a random-effects model, a DerSimonian-Laird meta-analysis for mean age difference across all studies was conducted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently less than 20% of individuals that could benefit from hearing aids use them (Popelka et al, 1998;Chien and Lin, 2012), suggesting that there is a large potential pool of individuals that could benefit from early intervention to limit the impact of ARHL, and therefore potentially lower the incidence of AD. Consistent with the potential benefits of early and aggressive intervention to treat ARHL is the finding that cochlear implantation may enhance overall cognitive function in elderly patients with hearing loss (Utoomprurkporn et al, 2020;Knopke et al, 2021;Mertens et al, 2021). The animal literature is generally supportive of the finding that induction of HL can cause more global cognitive dysfunction, but does not generally lead to a progressive degenerative phenotype (reviewed by Nadhimi and Llano, 2020).…”
Section: Introductionmentioning
confidence: 89%